Teleconsultations in the Brazilian market - Castro, Pedro Henrique de (2021)
The Brazilian healthcare industry is currently experiencing a digital transformation. Accelerated by the COVID-19 pandemic, the implementation of teleconsultation is becoming closer to being a reality. Due to the quarantine scenario, the government was obliged to temporarily officialize the practice of teleconsultation for all doctors and healthcare practitioners. Accordingly, accessibility between doctors and patients and efficiency in time and monetary conditions will be improved by this innovative care and treatment concept. Teleconsultation enables a time and location-independent treatment of patients using the digital world. However, this kind of digital medical treatment is currently not properly available in Brazil outside the pandemic period. This could be the time that shows the potential and need for implementation of this innovation. Therefore, this study assesses the current status and potential of teleconsultation in the Brazilian market, observing its great potential due to the vast physical territory that lacks quality healthcare assistance and the number of people paying for private insurance plans. Also, the findings of the study in terms of the main roadblocks for implementation shows that key barriers are created by stakeholders such as the government, insurance companies, doctors themselves and the technology providers. All of these play a decision-making role for implementing this healthcare method. Moreover, the Brazilian sample interviewed showed great acceptance of the innovation and the data collected together with the expert interviews indicated having this technology fully implemented within 5 years, at least in the main regions of the country.